U.S. Dental Hygiene Faculty Perceptions of Learner Outcomes in Distance Education Courses. Issue 4 (1st April 2014) - Corum, Kathrine A.; Gadbury‐Amyot, Cynthia C.; Johnson, Kerry; Strait, Tia M.
Abstract : The purpose of this study was to determine perceptions of full‐time, entry‐level dental hygiene educators regarding the ability to achieve interaction in their distance education courses and the impact of interaction on learning outcomes. The specific interactions explored were student‐instructor, student‐content, and student‐student. A survey was developed, pilot tested, revised, and mailed to 287 educators across the United States, generating an overall response rate of 22.3 percent. The majority of respondents perceived interaction to be achievable in their distance courses, to increase through technology, and to positively influence learning outcomes. Nearly 90 percent reported student‐instructor interaction as achievable, 95.3 percent reported student‐content interaction as achievable, and 79.7 percent reported student‐student interaction as achievable. Learning outcomes were defined in this study as the student's achievement of course objectives and competencies at course completion. Approximately 81 percent of the respondents reported a positive influence from student‐instructor interaction, 79.7 percent from student‐content interaction, and 70.3 percent from student‐student interaction. This study also examined which modalities were perceived as being most influential in achieving interaction. The results demonstrated a prevalence of discussion board posting in an environment in which numerous Web 2.0 tools are available and respondents were not as positive about their ability to achieve student‐student interaction in the distance learning environment. The authors conclude that faculty development is critical in achieving quality outcomes in dental hygiene distance education courses.